2020
DOI: 10.3390/cancers12061692
|View full text |Cite
|
Sign up to set email alerts
|

Integrated Assessment of Circulating Cell-Free MicroRNA Signatures in Plasma of Patients with Melanoma Brain Metastasis

Abstract: Primary cutaneous melanoma frequently metastasizes to distant organs including the brain. Identification of cell-free microRNAs (cfmiRs) found in the blood can be used as potential body fluid biomarkers for detecting and monitoring patients with melanoma brain metastasis (MBM). In this pilot study, we initially aimed to identify cfmiRs in the blood of MBM patients. Normal donors plasma (healthy, n = 48) and pre-operative MBM patients’ plasma samples (n = 36) were compared for differences in >2000 microRNAs … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
19
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 21 publications
(20 citation statements)
references
References 55 publications
1
19
0
Order By: Relevance
“…Only plasma samples were included in the study and from this point on all the samples will be referred to as plasma. The samples were all analyzed using the HTG EdgeSeq miR WTA [ 32 ]. All of the patients analyzed had a median follow-up of 9.7 months and received CII (ipilimumab, nivolumab, pembrolizumab, or the combination of ipilimumab and nivolumab) as first line treatment.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Only plasma samples were included in the study and from this point on all the samples will be referred to as plasma. The samples were all analyzed using the HTG EdgeSeq miR WTA [ 32 ]. All of the patients analyzed had a median follow-up of 9.7 months and received CII (ipilimumab, nivolumab, pembrolizumab, or the combination of ipilimumab and nivolumab) as first line treatment.…”
Section: Resultsmentioning
confidence: 99%
“…In evaluating the utility of cfmiRs, it is important to find cfmiRs that have applicability in real-time monitoring of melanoma patient’s disease status before and during CII(s) to evaluate response. Recently, we have shown that specific cfmiR patterns found in MBM patients’ plasma may have utility in monitoring melanoma patients undergoing treatment [ 32 ]. Our hypothesis is that specific cfmiRs have a better utility compared to serum LDH levels in the assessment of melanoma patients undergoing CII.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations